Combined effects of cellulose nanofiber nucleation and maleated polylactic acid compatibilization on the crystallization kinetic and mechanical properties of polylactic acid nanocomposite - Shazleen, Siti Shazra; Ng, Lawrence Yee Foong; Ibrahim, Nor Azowa; Hassan, Mohd Ali; Ariffin, Hidayah (Multidisciplinary Digital Publishing Institute, 2021)
This work investigated the combined effects of CNF nucleation (3 wt.%) and PLA-g-MA compatibilization at different loadings (1–4 wt.%) on the crystallization kinetics and mechanical properties of polylactic acid (PLA). A crystallization kinetics study was done through isothermal and non-isothermal crystallization kinetics using differential scanning calorimetry (DSC) analysis. It was shown that PLA-g-MA had some effect on nucleation as exhibited by the value of crystallization half time and crystallization rate of the PLA/PLA-g-MA, which were increased by 180% and 172%, respectively, as compared to neat PLA when isothermally melt crystallized at 100 °C. Nevertheless, the presence of PLA-g-MA in PLA/PLA-g-MA/CNF3 nanocomposites did not improve the crystallization rate compared to that of uncompatibilized PLA/CNF3. Tensile strength was reduced with the increased amount of PLA-g-MA. Contrarily, Young’s modulus values showed drastic increment compared to the neat PLA, showing that the addition of the PLA-g-MA contributed to the rigidity of the PLA nanocomposites. Overall, it can be concluded that PLA/CNF nanocomposite has good performance, whereby the addition of PLA-g-MA in PLA/CNF may not be necessary for improving both the crystallization kinetics and tensile strength. The addition of PLA-g-MA may be needed to produce rigid nanocomposites; nevertheless, in this case, the crystallization rate of the material needs to be compromised.